2016
DOI: 10.1186/s13052-016-0285-0
|View full text |Cite
|
Sign up to set email alerts
|

Daily life changes and adaptations investigated in 154 families with a child suffering from a rare disability at a public centre for rare diseases in Northern Italy

Abstract: BackgroundLiving with a disabled child has profound effects on the entire family. With a prevalence of developmental disabilities around 2,5 %, there is a considerable need to promote improvements in the health care system. Little is known about changes and adaptations in the lives of affected families and this paucity of information hinders the improvement of services. This study sought to explore the needs and changes in the everyday life of families with children suffering from rare diseases of varying seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
1
29
0
6
Order By: Relevance
“…At last, like other studies conducted with students with special educational needs (Gül & Vuran, ; McConkie et al., ; Silibello et al., ), the results of this research highlight the need for coordinated work at different levels. Within the school, this coordination must exist, between teachers in different levels and between the different professionals in the school setting (peripatetic teaching staff, support teachers, etc.).…”
Section: Discussionsupporting
confidence: 81%
“…At last, like other studies conducted with students with special educational needs (Gül & Vuran, ; McConkie et al., ; Silibello et al., ), the results of this research highlight the need for coordinated work at different levels. Within the school, this coordination must exist, between teachers in different levels and between the different professionals in the school setting (peripatetic teaching staff, support teachers, etc.).…”
Section: Discussionsupporting
confidence: 81%
“…This study confirmed both the existence of pupils with RDs in ordinary schools and that of an educational response aimed at them. However, despite the existence of this response, parents with severely disabled children were less happy with the education system than the rest and considered family-centred attention and multidisciplinary work to be essential (Silibello et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, only six (Barrio and Castro, 2008;Han, 2008;Lee and Lee, 2014;Lin et al, 2013;Silibello et al, 2016;Waldman et al, 2008) of the studies analysed were at all related or included any information of interest to the education/school sphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En este último ámbito, los cambios que conlleva la evolución de la enfermedad hacen que en algunas de las situaciones la atención educativa no sea la adecuada, o dentro del marco inclusivo recomendado. A pesar de que la incidencia de estudiantes con enfermedades raras está incrementando significativamente en los niños de 3 a 14 años (Darretxe, Gaintza, & Monzón-González, 2017), y aunque la respuesta educativa se ofrece en los colegios ordinarios generalmente, los padres no están conformes con el sistema educativo y consideran esencial el trabajo multidisciplinar y centrado en la familia (Silibello, Vizziello, Gallucci, et al, 2016).…”
Section: Discusión Y Conclusionesunclassified